A comparison of longitudinal controllers for autonomous UAV - Vural, S. Yenal; Hajiyev, Chingiz (Inderscience Publishers, 2014)
This paper describes the design of an altitude control system for a small unmanned aerial vehicle (UAV) using classical control methods, optimal control methods and fuzzy logic. A survey on recent research is made to develop a better UAV control system. A small radio control (RC) plane that is converted to a small UAV for testing purposes is used. The equations of motion of the UAV and state-space realisation of the system are included in the study. The longitudinal stability characteristic of the small UAV is analysed and classical control method using proportional-derivative (PD) controller, linear quadratic regulator (LQR) type optimal controller using different weight matrices and fuzzy logic controller are designed. The effectiveness of different control methods in this case is investigated and the results of the altitude control systems are compared.